Respuesta :

Step-by-step explanation:

Given that:

∛(2) * 2^(-1/13) * ¹²√(32)

= ∛(2) * 2^(-1/13) * ¹²√(2⁵)

[since, ⁿ√(a) = a^(1/n)]

= 2^(1/3) * 2^(-1/13) * 2^{5 * (1/12)}

= 2^(1/3) * 2^(-1/13) * 2^{(5*1)/12}

= 2^(1/3) * 2^(-1/13) * 2^(5/12)

[since, a^m * a^n = a^(m+n)]

= 2^{(1/3) - (1/13) + (5/12)}

Take the LCM of 3, 13 and 12 is 156.

= 2^[{(1*52) - (1*12) + (5*13)}/156]

= 2^{(52 - 12 + 65)/156}

= 2^{(117 - 12)/156}

= 2^(105/156)

Now reduce the power fraction in simplest form by cancelling method.

= 2^(35/52) (or)

= {2^(35)}^(1/52) (or)

= ⁵²√{2^(35)}

Answer: Hence, the simplified form of ∛(2) * 2^(-1/13) * ¹²√(32) = ⁵²√{2^(³⁵)}.

Please let me know if you have any other questions.

[tex]\sqrt[3]{2}[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]\sqrt[12]{32}[/tex] = [tex]2^{\frac{35}{52} }[/tex]

Applying law of indices

Applying the law of indices to the roots, we have that

[tex]\sqrt[n]{x} = x^{\frac{1}{n} }[/tex]

So,

[tex]\sqrt[3]{2}[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]\sqrt[12]{32}[/tex] = [tex]2^{\frac{1}{3} }[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]32^{\frac{1}{12} }[/tex]

=  [tex]2^{\frac{1}{3} }[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex](2^{5} )^{\frac{1}{12} }[/tex]

= [tex]2^{\frac{1}{3} }[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]2^{\frac{5}{12} }[/tex]

Since we have the same base in all three numbers, we have that from the law of indices, [tex]a^{x}[/tex] × [tex]a^{y}[/tex] = [tex]a^{x + y}[/tex]

= [tex]2^{\frac{1}{3} }[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]2^{\frac{5}{12} }[/tex]

[tex]= 2^{\frac{1}{3} + (-\frac{1}{13}) + \frac{5}{12} } \\= 2^{\frac{1}{3} - \frac{1}{13} + \frac{5}{12} }[/tex]

Taking L..C.M of the denominators of the exponents, the L.C.M is 156.

So,

[tex]2^{\frac{1}{3} - \frac{1}{13} + \frac{5}{12} }\\= 2^{\frac{52 - 12 + 5 X 13}{156} } \\= 2^{\frac{52 - 12 + 65}{156} }\\= 2^{\frac{40 + 65}{156} }\\= 2^{\frac{105}{156} }[/tex]

Simplifying the exponent, we have

[tex]2^{\frac{105}{156} } \\= 2^{\frac{35}{52} }[/tex]

So, [tex]\sqrt[3]{2}[/tex] × [tex]2^{-\frac{1}{13} }[/tex] × [tex]\sqrt[12]{32}[/tex] = [tex]2^{\frac{35}{52} }[/tex]

Learn more about indices here:

https://brainly.com/question/10339517